The aluminium-[18F]fluoride revolution: simple radiochemistry with a big impact for radiolabelled biomolecules - Stephen J. Archibald; Louis Allott (SpringerOpen, 2021)
Abstract The aluminium-[18F]fluoride ([18F]AlF) radiolabelling method combines the favourable decay characteristics of fluorine-18 with the convenience and familiarity of metal-based radiochemistry and has been used to parallel gallium-68 radiopharmaceutical developments. As such, the [18F]AlF method is popular and widely implemented in the development of radiopharmaceuticals for the clinic. In this review, we capture the current status of [18F]AlF-based technology and reflect upon its impact on nuclear medicine, as well as offering our perspective on what the future holds for this unique radiolabelling method.